Genetics, Transcriptomics and Meta-Taxonomics in Visceral Leishmaniasis - Blackwell, Jenefer M.; Fakiola, Michaela; Singh, Om Prakash (Frontiers in Cellular and Infection Microbiology, 2020)
Visceral leishmaniasis (VL) is a potentially fatal disease caused by parasites of the Leishmania donovani complex. Understanding the interactions between host and pathogen could provide important leads for improved therapies and vaccines. In recent years multiple omics-based approaches have assisted researchers to gain a more global picture of this interaction in leishmaniasis. Here we review results from studies using three omics-based approaches to study VL caused by L. donovani in India: (i) chip-based analysis of single nucleotide variants in the first genome-wide association study of host genetic risk factors for VL, followed by analysis of epitope binding to HLA DRB1 risk versus protective alleles; (ii) transcriptional profiling demonstrating pathways important in Amphotericin B treated compared to active VL cases, including demonstration that anti-interleukin-10 unleashes a storm of chemokines and cytokines in whole blood responses to soluble leishmania antigen in active cases; and (iii) a meta-taxonomic approach using amplicon-based sequencing of 16S ribosomal RNA (16S rRNA) and 18S rRNA gene regions that allowed us to look at the composition of both prokaryotic and eukaryotic gut microflora in VL cases compared to endemic controls. Overall, our omics-based approaches demonstrate that global analyses of genetic risk factors, host responses to infection, and the interaction between host, parasite and the microbiome can point to the most critical factors that determine the outcome of infection.